Pelatihan Brief Psychoeducation bagi Kader Warga Peduli AIDS (WPA) Genuksari dalam Mengurangi Stigma Masyarakat terhadap Orang dengan Human Immunodeficiency Virus (ODHIV): Brief Psychoeducation Training for Warga Peduli AIDS (WPA) Genuksari Cadres in Reducing Community Stigma among People Living With Human Immunodeficiency Virus (PLHIV) - Ahmad Ikhlasul Amal; Dwi Retno Sulistyoningsih; Retno Setyawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Stigma in PLHIV is often shown by social rejection, lack of recognition, and discrimination that will cause shame and fear for PLHIV to interact with others. HIV-positive status can lead to a lack of social support, lead to depression, loss of opportunities to work and earn income, and decreased courage to seek medical services. Residents Concerned about AIDS (WPA) of Genuksari Village are one of the PLHIV support groups that have the potential to reduce community stigma. One of the efforts to increase the ability of WPA Genuksari members is to assist. In this assistance, efforts will be made to screen HIV risk in healthy communities, screen stigma in the community, and increase the ability to overcome community stigma through brief psychoeducation.